Participation in real-world laboratories in a new light?!: Closing the gap between co-creative and deliberative participation - Marco Sonnberger; Doris Lindner (Raumforschung und Raumordnung / Spatial Research and Planning, 2021)
Sustainability-oriented real-world laboratories involve the co-design and co-creation of knowledge, based on a trans- disciplinary cooperation between actors from different social worlds-academia,theadministration,business,civilsociety- each endowed with specific interests, resources and world- views. Sustainability-oriented real-world laboratories claim to be a means of inclusive participation in the co-creative shaping of solutions for socioecological issues and exploring pathways to sustainability. In the literature dealing with sus- tainability-oriented real-world laboratories, participation is thus mainly understood as active involvement by civil society, change agents and citizens in processes of experimentation and the implementation of solutions. We call this co-creative participation. However, participation in talk-based opinion formation and decision-making processes - we call this de- liberative participation - is hardly discussed in the respective literature. In this paper, we argue that co-creative and delib- erative participation are two forms of participation which can be conceptualized differently but which are both relevant for successful experimentation in sustainability-oriented real- world laboratories and are mainly intertwined in practice. We propose an ideal-typical conceptual framework for par- ticipation in sustainability-oriented real-world laboratories that combines co-creative and deliberative participation. The aim is to contribute to a systematization of, and rationale for, different forms of participation in real-world laboratories. – – Basierend auf der transdisziplinären Kooperation von Akteuren aus unterschiedlichen Feldern (Wissenschaft, Verwaltung, Wirtschaft, Zivilgesellschaft), die sich jeweils durch spezifische Interessen, Weltsichten und Ressourcenausstattungen auszeichnen, zielen Reallabore auf das Co-Design und die Co-Kreation von Wissen ab. Damit ist der Anspruch verbunden, dass Reallabore ein Mittel inklusiver Partizipation in der co-kreativen Lösungsfindung für sozialökologische Probleme sein sollen. In der aktuellen Literatur zu Reallaboren wird Partizipation zumeist als aktive Beteiligung von Zivilgesellschaft, Pionier*innen des Wandels und Bürger*innen in praktischen Prozessen des Experimentierens und der Implementation von Problemlösungen verstanden. Wir bezeichnen dies als co-kreative Partizipation. Formen dialogbasierter Meinungsbildung und Entscheidungsfindung (deliberative Partizipation) finden in der einschlägigen Literatur dagegen kaum Beachtung. In diesem Artikel argumentieren wir, dass co-kreative und deliberative Partizipation zwei unterschiedlich verfasste Formen von Partizipation sind, die jedoch beide von Relevanz für den Erfolg eines Reallabors sind. Basierend auf unseren praktischen Erfahrungen im Reallabor für nachhaltige Mobilitätskultur (RNM) erarbeiten wir einen idealtypischen konzeptionellen Rahmen, der co-kreative und deliberative Partizipationsformen in Beziehung zueinander setzt und so eine Systematisierung und Begründung unterschiedlicher Partizipationsformen in Reallaboren liefert.
Keywords: 710; Reallabore; Co-Kreation; Partizipation; Deliberation; Realexperimente